MRI-Based Optimization Design of the Pre-Spinal Route of Contralateral C7 Nerve Transfer for Spastic Arm Paralysis - Zhao, Hua-Li; Gao, Yun; Yu, Ai-Ping; Wei, Yi-Min; Shen, Yun-Dong; Jiang, Su; Qiu, Yan-Qun; Yu, Jing; Liang, Zong-Hui (Frontiers in Surgery, 2022)
Purpose The prespinal route of contralateral cervical 7 nerve transfer developed by Prof. Wendong Xu helps realize the direct anastomosis of the bilateral cervical 7 nerves. However, 20% of operations still require a nerve graft, which leads to an unfavorable prognosis. This study aims to explore the optimized prespinal route with MRI to further improve the prognosis. Methods The current study enrolled 30 patients who suffered from central spastic paralysis of an upper limb and who underwent contralateral cervical 7 nerve transfer via Prof. Xu’s prespinal route through the anterior edge of the contralateral longus colli. MRI images were used to analyze the route length, vertebral artery exposure, and contralateral cervical 7 nerve included angle. Three prespinal routes were virtually designed and analyzed. The selected optimal route was applied to another 50 patients with central spastic paralysis of an upper limb for contralateral cervical 7 nerve transfer. Results By the interventions on the 30 patients, the middle and posterior routes were shorter than the anterior route in length, but with no statistical difference between the two routes. Of 30 contralateral vertebral arteries, 26 were located at the posterior medial edge of the longus colli. The average included angles of the anterior, middle, and posterior routes were 108.02 ± 7.89°, 95.51 ± 6.52°, and 72.48 ± 4.65°, respectively. According to these data, the middle route was optimally applied to 50 patients, in whom the rate of nerve transplantation was only 4%, and no serious complications such as vertebral artery or brachial plexus injury occurred. Conclusion The low rate of nerve transplantation in 50 patients and the absence of any serious complications in these cases suggests that the middle route is the optimal one.